Perceived Realism in Dubbing Classroom of the Elite in Increasing Viewer Enjoyment - Cesar Rafelino, Kevin; Kurnia (Zona Education Indonesia, 2024)
The need for dubbing on streaming platforms continues to increase due to the increase in the production of multilingual content to attract new viewers. In accordance with this phenomenon, the objectives of this study are (1) to determine the effect of perceived realism on dubbing Classroom of the Elite on viewers enjoyment, (2) to determine how much influence perceived realism on dubbing Classroom of the Elite has on viewers enjoyment. This study uses a convinience sampling method with the sample criteria involving people who know and watch the Classroom of the Elite anime dubbed into Indonesian. Lemeshow's calculation method with a 10% error is applied in determining the sample size. The results showed that perceived realism in Classroom of the Elite dubbing affects viewers enjoyment. enjoyment of animated shows can be increased by applying dubbing that has good perceived realism. perceived realism in dubbed shows can be built from a number of elements, namely perceptual quality, plausibility, narrative consistency, typicality and factuality. This shows that dubbed shows must be plausible with narrative coherence that has distinctiveness, and in accordance with reality